REDUCING AMMONIA CONCENTRATIONS IN ATMOSPHERE AFTER ITS UNPLANNED RELEASE - Amelina, L. V.; Biliaiev, M. M.; Mashykhina, P. B. (Science and Transport Progress, 2017)
Purpose. The aim of this work is development of numerical model, which allows to calculate the efficiency of neutralizer supply for reduction of air pollution in case of unplanned ammonia emission at the territory of ammonia pump station. The numerical model should allow fast calculating, taking into account the meteorological parameters and buildings situated near the source of toxic chemical emission and equipment for neutralizer supply. Methodology. The developed model is based on the equation for potential flow and equation of pollutant dispersion. To simulate the chemical interaction between ammonia and neutralizer the stoichiometry equation is used. Equation of potential flow is used to compute flow pattern among buildings. To solve the equation for potential flow the Samarskii implicit difference scheme is used. The implicit change-triangle difference scheme is used to solve equation of mass transfer. While for the numerical integration the authors use the rectangular difference grid. Method of porosity technique («markers method») is applied to create the form of comprehensive computational region. Emission of ammonia is modeled using Delta function for point source. Findings. Developed numerical model belongs to the class of «diagnostic models». This model takes into account the main physical factors affecting the process of dispersion of ammonia and neutralizer in the atmosphere, as well as the influence of buildings on admixture dispersion. On the basis of the developed numerical models the authors carried out a computational experiment to estimate the efficiency of neutralizer supply for reduction of air pollution in case of unplanned ammonia release at ammonia pump station. Originality. Developed numerical model allows calculating the flow pattern among buildings and estimating the efficiency of neutralizer supply for reduction of air pollution in the case unplanned ammonia release. Practical value. Model allows performing fast calculations of the atmosphere pollution in the case of unplanned ammonia release